Band-Notched Ultrawide Band Planar Inverted-F Antenna - H. T. Chattha; M. K. Ishfaq; Y. Saleem; Y. Huang; S. J. Boyes (International Journal of Antennas and Propagation)
A novel ultrawide band planar inverted-F antenna with band-notched characteristics is presented in this paper. The planar inverted-F antenna uses two parasitic elements to enhance the bandwidth to cover the ultrawide band. The band-notched feature is added by inserting a W-shaped slot on the top radiating element of the antenna with a band rejection from 5.08 to 6 GHz (measured). Both the measured and simulated results are obtained to draw the conclusions.